UJI AKTIVITAS ANTIOKSIDAN EKSTRAK ETIL ASETAT DAUN KARAMUNTING (MELASTOMA MALABATCHRICUM L.) DENGAN METODE ABTS - Muthia, Rahmi; Azhari, Fajar; Bin Jamaludin, Wahyudin (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2023)
Antioxidants are compounds that function to neutralize oxidized compounds by capturing free radicals in the body so that they do not cause disease. Due to the negative effects of synthetic antioxidants, people use other alternatives with natural antioxidants found in plants. Karamunting leaf extract has great antioxidant activity. To determine the secondary metabolite content contained in the ethyl acetate extract of caramunting leaves and determine the IC50 value obtained from the antioxidant activity test of caramunting leaves. Identification of compounds using phytochemical screening methods. This antioxidant test method uses ABTS reagent (2,2-azinobis-3-ethylbenzothiazoline-6-sulfonate) and potassium persulfate which are analyzed with a UV-Vis spectrophotometer. The comparator used was quercetin. The results of phytochemical screening showed that the ethyl acetate extract of caramunting leaves (Melastoma malabathricum L.) contained alkaloids, flavonoids, phenols, saponins and steroids. The results of determining λmax are 745 nm and the operating time measurement results are 38 - 42 minutes. The IC50 values ​​of ethyl acetate extract of caramunting leaves and quercetin were 2.2419 µg/mL and 2.6821 µg/mL respectively. The antioxidant activity of ethyl acetate extract of caramunting leaves is classified as very strong.